Mantle transcriptome sequencing of Mytilus spp. and identification of putative biomineralization genes - Magdalena Malachowicz; Roman Wenne (PeerJ, 2019)
In molluscs, the shell secreted by mantle tissue during the biomineralization process is the first barrier against predators and mechanical damage. Changing environmental conditions, such as ocean acidification, influence shell strength and thus protection of the soft body within. Mussels are marine bivalves with important commercial and ecological value worldwide. Despite this importance, the proteins involved in the biomineralization and pigmentation processes in Mytilus spp. remain unclear, as does taxonomy of Mytilus taxa, though there have been many molecular studies. To further understanding in these areas, this study aimed to characterize and compare mantle transcriptomes of four mussel taxa using next generation sequencing. Mussels representing four taxa, were collected from several localities and RNA from mantle tissue was extracted. RNA sequences obtained were assembled, annotated and potential molecular markers, including simple sequence repeats (SSRs) and single nucleotide polymorphisms (SNPs) were identified. Candidate contigs putatively related to biomineralization and pigmentation processes were then selected and several transcripts were chosen for phylogenetic analyses from the Bivalvia class. Transcriptome comparisons between Mytilus taxa, including gene ontology (GO) enrichment analysis and orthologues identification were performed. Of assembled contigs, 46.57%, 37.28% and 17.53% were annotated using NCBI NR, GO and Kyoto Encyclopedia of Genes and Genomes databases, respectively. Potential SSRs (483) and SNPs (1,497) were identified. Results presented a total of 1,292 contigs putatively involved in biomineralization and melanogenesis. Phylogenetic analyses of α-carbonic anhydrase, chitinase and tyrosinase revealed complex evolutionary history and diversity of these genes, which may be a result of duplication events or adaptation to different environments in mussels and other bivalves. Enrichment analyses revealed GO terms associated with pH and thermal response in Mytilus edulis from the North Sea and M. galloprovincialis from the Mediterranean Sea. The phylogenetic analysis within the genus Mytilus revealed M. californianus and M. coruscus to be genetically more distant from the other taxa: M. trossulus, M. edulis, M. chilensis and M. galloprovincialis. This work represents the first mantle transcriptome comparison between Mytilus taxa and provides contigs putatively involved in biomineralization.